PENGARUH PENERAPAN TEKNIK QUICK ON THE DRAW TERHADAP MOTIVASI DAN HASIL BELAJAR MATEMATIKA SISWA KELAS IX (JURNAL LEMMA, 2018)
This research was based on the students’ result of learning Mathematics that were still low, lack of motivation and participation from the students in the teaching learning process. This research was aimed to know how students’ motivation in learning Mathematics by applying Quick On The Draw technique at grade IX  and to know whether the students’ result of learning Mathematics by applying Quick On The Draw technique better than students’ result of learning Mathematics by applying conventional learning. The type of this research was experimental research that used random design toward the subject. The population of this research was all the grade IX students of SMPN 2 Batang Anai. The sample of this research were two classes that were taken randomly. The instruments of the research were the motivation questionnaire and final test in the essay form. The motivation questionnaire were given in the last meeting of experiment class. The analysis of the data were done by finding the motivation score of each student and it is resulted that the students’ learning motivation had a very motivated criteria. Technique analysis of the data that was used tohypotheses test was t-test. Based on the hypotheses test, it is found that the hypotheses was accepted. Therefore, it can be concluded that the students’ result of learning Mathematics by applying Quick On The Draw technique was better than students’ result of learning Mathematics by applying conventional learning at grade IX